2005
DOI: 10.1177/0022427803262061
|View full text |Cite
|
Sign up to set email alerts
|

Violent Lives: A Lifestyle Model Linking Exposure to Violence to Juvenile Violent Offending

Abstract: Studies examining the consequences of juvenile exposure to violence focus largely on psychological outcomes and often ignore the ways in which exposure is associated with deviant peers and juvenile offending. Using data from the National Survey of Adolescents (NSA), a nationally representative sample of juveniles between the ages of 12 and 17, we examine the relationship between various types of exposure to violence and violent offending. Based on Hindelang, Gottfredson, and Garofalo’s Lifestyle model of victi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
99
1
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(106 citation statements)
references
References 40 publications
4
99
1
2
Order By: Relevance
“…This finding lends support to the idea of certain people being involved in ‗lifestyles of violence' (Nofziger and Kurtz 2005), an offshoot of the routine activity (Cohen and Felson 1979) and lifestyle (Hindelang, Gottfredson and Garofalo 1978) theories of crime, 9 which suggest that certain people, especially the young and males, may find themselves at increased risk of violence due to engagement in activities that make them more vulnerable, such as substance use and going out at night, as well as placing them in closer proximity to criminal offenders. As Felson writes, those going out at night, for instance, ‗may be more likely to engage in aggression, deviance, and other behaviors that others find offensive' and ‗Their provocative behavior may lead them to be the target of violence ' (1997: 209).…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…This finding lends support to the idea of certain people being involved in ‗lifestyles of violence' (Nofziger and Kurtz 2005), an offshoot of the routine activity (Cohen and Felson 1979) and lifestyle (Hindelang, Gottfredson and Garofalo 1978) theories of crime, 9 which suggest that certain people, especially the young and males, may find themselves at increased risk of violence due to engagement in activities that make them more vulnerable, such as substance use and going out at night, as well as placing them in closer proximity to criminal offenders. As Felson writes, those going out at night, for instance, ‗may be more likely to engage in aggression, deviance, and other behaviors that others find offensive' and ‗Their provocative behavior may lead them to be the target of violence ' (1997: 209).…”
Section: Resultssupporting
confidence: 73%
“…Studies in the U.S. (Jensen and Brownfield 1986;Sampson and Lauritsen 1990;Lauritsen, Sampson and Laub 1991;Shaffer and Ruback 2002;Plass and Carmody 2005), United Kingdom (Sampson and Lauritsen 1990), Iceland (Bjarnason, Sigurdardottir, and Thorlindsson 1999) and Colombia (Klevens, Duque and Ramirez 2002) have found that those engaging in criminal and deviant activity are more likely than the ‗average person' to have been victims of crime, and vice versa (Nofziger and Kurtz 2005). This may result from their association with other criminal types, involvement in gang activities, living in or frequenting violent locations, and the fact that offenders make attractive targets for criminal victimization because they will be less likely than ‗nonoffender-victims' to call the police, and if they do involve the authorities, their credibility will be called into question (Lauritsen et al 1991: 268).…”
Section: Victimization and Perpetrationmentioning
confidence: 99%
“…Desta forma, devido às suas atividades, rotinas e estilos de vida (Hindelang, Gottfredson, & Garofalo, 1978;Wilcox, 2010), estes indivíduos apresentam um maior risco de vitimação. Trata-se de estilos de vida que incluem inúmeras atividades no exterior, particularmente à noite, aumentando a probabilidade de se ser vítima de crime (Kennedy & Forde, 1990;Nofziger & Krutz, 2005). Não obstante, mais importante do que o lugar que se frequenta, parecem ser as pessoas com quem se mantém contacto e com as quais se estabelecem relações (Nofziger, 2009).…”
Section: Introductionunclassified
“…They proposed that victimisation was a function of lifestyles or the routines associated with work, school, or leisure activities (Nofziger & Kurtz, 2005;Wilcox, 2010 …”
Section: Lifestyle Theorymentioning
confidence: 99%